Expression of CD1d in human scalp skin and hair follicles: hair cycle related alterations. Issue 12 (25th November 2005) - Adley, M A; Assaf, H A; Hussein, M
Abstract : Background: CD1d belongs to a family of antigen presenting molecules that are structurally and distantly related to the classic major histocompatibility complex class I (MHC I) proteins. However, unlike MHC I molecules, which bind protein antigens, CD1d binds to lipid and glycolipid antigens. CD1d is expressed by cells of lymphoid and myeloid origin, and by cells outside of the lymphoid and myeloid lineages, such as human keratinocytes of psoriatic skin. Aims: To investigate whether CD1d is also expressed in sun exposed skin and in the immunoprivileged anagen hair follicle. Materials/Methods: CD1d immunoreactivity was studied in human scalp skin and hair follicles of healthy women in situ by immunofluorescent and light microscopic immunohistology. Skin biopsies were obtained from normal human scalp containing mainly anagen VI hair follicles from women (age, 53–57 years) undergoing elective plastic surgery. Results: CD1d showed strong immunostaining in human scalp skin epidermis, pilosebaceous units, and eccrine glands. In the epidermis, CD1d was strongly expressed by basal and granular keratinocytes. In hair follicles, CD1d was expressed in the epithelial compartment and showed hair cycle related alterations, with an increase in the anagen and a reduction in the catagen and telogen phases. Conclusions: These results suggest that CD1d plays a role in human scalp skin immunology and protection against lipid antigen rich infectious microbes. They also raise the question of whether keratinocytes of the immunoprivileged anagen hair follicle can present lipid antigens to natural killer T cells. These data could help provide new strategies for the manipulation of hair related disorders.